2015
DOI: 10.1016/j.aquatox.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Timing matters: Sensitivity of Daphnia magna dormant eggs to fenoxycarb exposure depends on embryonic developmental stage

Abstract: Although Daphnia magna is a key species in many lentic freshwater ecosystems and is commonly used as model organism in ecology and ecotoxicology, very little is known about the effects of chemicals on their dormant life stages. Dormant eggs (ephippia) are produced when environmental conditions deteriorate, and Daphnia switch from clonal to sexual reproduction. Ephippia produced over different growing seasons can accumulate in the sediment of ponds and lakes, where they can be exposed to pesticides and other (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Previously, effects of pesticides and sedimentary metals have been observed on development and hatching success of the diapausing eggs of cladocerans Daphnia (Navis et al 2013(Navis et al , 2015Rogalski 2015). Additionally, a field study showed metals were accumulated by Daphnia ephippia (Wyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, effects of pesticides and sedimentary metals have been observed on development and hatching success of the diapausing eggs of cladocerans Daphnia (Navis et al 2013(Navis et al , 2015Rogalski 2015). Additionally, a field study showed metals were accumulated by Daphnia ephippia (Wyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These antecedents suggest that toxicants are incorporated to diapausing stages from the medium, and that even though diapausing stages facilitate the survival of aquatic organisms under extreme conditions due to suppressed metabolism, there is contradictory evidence about the resistance to toxic agents in zooplankton embryonic development when embryos are still inside protective membranes. While Alekseev et al (2010) showed great capability of diapausing eggs to resist severe pollution events in several zooplankton groups, Navis et al (2015) suggested that the cladoceran ephippium offers limited protection against pesticides dissolved in the medium. Moreover, pesticide bioconcentration in the eggs increases with exposure time during the embryonic development (Navis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…crowding or changes in photoperiod). Development of the resting stage arrests at the onset of gastrulation, at the ∼1000-cell stage (Baldass, 1941), with the embryo contained in a protective, inflexible tertiary egg membrane in addition to the two membranes found around directly developing parthenogenetic eggs (Navis et al, 2015). These ephippial embryos can then persist for periods of days to decades and be dispersed to new habitats, surviving drying, temperature extremes, anoxia and chemical exposure.…”
Section: Introductionmentioning
confidence: 99%